PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TPS PADA MATERI FUNGSI DI KELAS X SMAN 9 PONTIANAK - Andini, Indri Desti; Zubaidah, Zubaidah; Ijuddin, Romal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to know the effectiveness of the implementation of cooperative learning think pair share type in function topic at class X SMA Negeri 9 Pontianak. The research method used is pre-experimental method with the one-shot case study design. The aspect used to determine the effectivennes of the cooperative learning think pair share type are teacher’s class management, student’s activity, and student’s outcomes. The data collection tools used are test student’s outcomes which countains 7 essay and the observastion sheet for teacher’s class management and student’s activity. The result of the descriptive analysis carried out are teacher’s class management categorized good (3,35), sudent’s activity categorized active (73,74%), and student’s completeness not fulfilled classically (only 25 students or 76% students can fulfill the standard completeness). Because there was one aspect that not fulfilled, so the implementation of cooperative learning think pair share type in function topic at class X SMA Negeri 9 Pontianak was not effective. Keywords: Cooperative, Think Pair Share, Function